Reproduction and longevity: A Mendelian randomization study of gonadotropin-releasing hormone and ischemic heart disease - C.M. Schooling; Jack C.M. Ng (Elsevier, 2019)
Background: According to well-established evolutionary biology theory there is a trade-off between reproduction and longevity, implying that upregulating the reproductive axis might drive major diseases. We assessed whether the central driver of reproduction gonadotropin-releasing hormone 1 (GnRH1) had a causal effect on the leading cause of global morbidity and mortality, i.e. ischemic heart disease (IHD). As a contrast we similarly examined the role of GnRH2 because it is more a driver of female sexual behavior. Methods: We applied strong (p-value <5 × 10−6) and independent genetic predictors of GnRH1 and GnRH2 to an extensively genotyped IHD case (n = 76,014) - control (n = 264,785) study and combined the genetic variant specific Wald estimates using inverse variance weighting (IVW) with multiplicative random effects, and as a sensitivity analysis used weighted median, MR-Egger and MR-PRESSO estimates, and repeated the analysis only using genome wide significant genetic predictors. Findings: GnRH1, predicted by 11 genetic variants, was positively associated with IHD (IVW odds ratio (OR) 1.04 per effect size, 95% confidence interval (CI) 1.01 to 1.08), but GnRH2, predicted by 15 genetic variants, was not (IVW OR 0.98, 95% CI 0.95 to 1.02). Estimates from sensitivity analysis were similar. Interpretation: GnRH1 is a potential IHD genetic target. Apart from demonstrating a central tenet of evolutionary biology in humans, our study suggests that existing treatments and environmental factors targeting GnRH1, its drivers or consequences could be re-purposed to prevent and treat IHD. Given, the importance of reproduction to the human species, many such exposures likely exist. Keywords: GnRH, IHD, Mendelian randomization, Evolutionary biology